Praktik Green Accounting dan Economic Value Added terhadap Firm Value - Azwani Aulia; Rosa Fitriana (LPPM UNIBI, 2023)
Environmental problems are now increasing due to the lack of corporate responsibility in managing the impacts of their operational activities. The spread of environmental problems has increased public concern for the environment. Therefore, the government holds the Green Industry awards every year to encourage business people to apply the Green Economy concept which is used as a solution to overcome environmental problems. The aim of this research is to test and analyze the influence of Green Accounting and Economic Value Added partially and simultaneously on company value. This type of research is quantitative with a descriptive approach. The data used is the annual report obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id and the official website of each mining sector company for 2018-2022. The sampling technique used purposive sampling so that 75 samples were obtained from 15 mining sector companies. Data testing techniques use descriptive statistical analysis, classical assumption testing, multiple linear regression, correlation coefficient, coefficient of determination and hypothesis testing. Research shows that green accounting and economic value added partially influence company value. Meanwhile, green accounting and economic value added simultaneously influence company value.